ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS PADA PESERTA DIDIK KELAS X SMK NEGERI 7 PALEMBANG - Dian Cysarah; Jumroh Jumroh; Destiniar Destiniar (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2021)
This study aims to find out the mathematical critical thinking ability of students of class X SMK Negeri 7 Palembang. The sample of 32 students in class X Motorcycle Engineering 1. Data collection techniques using test questions in the form of description of linear equation system material two variables as much as 3 points. The results showed that in the ability indicators provide a simple explanation of 78.47% categorized as high, basic skill building indicators of 94.44% are categorized very high, indicators make further explanations of 90.27% categorized very high, indicators set strategies and tactics by 58.68% categorized moderately, and indicators concluded at 27.08% categorized as low. Meanwhile, the average mathematical critical thinking ability of learners was 73.81% in the high category.